Will COVID‐19‐related economic worries superimpose health worries, reducing nonpharmaceutical intervention acceptance in Germany? A prospective pre‐registered study. (16th March 2021) - Rosman, Tom; Kerwer, Martin; Steinmetz, Holger; Chasiotis, Anita; Wedderhoff, Oliver; Betsch, Cornelia; Bosnjak, Michael
Abstract : Nonpharmaceutical interventions (NPI) such as stay‐at‐home orders aim at curbing the spread of the novel coronavirus, SARS‐COV‐2. In March 2020, a large proportion of the German population supported such interventions. In this article, we analyse whether the support for NPI dwindle with economic worries superimposing virus‐related worries in the months to follow. We test seven pre‐registered 1 hypotheses using data from the German COSMO survey (Betsch, Wieler, Habersaat, et al. 2020), which regularly monitors behavioural and psychological factors related to the pandemic. The present article covers the period from March 24, 2020 to July 7, 2020 ( N total = 13, 094), and, in addition, includes a validation study providing evidence for the reliability and validity of the corresponding COSMO measures ( N = 612). Results revealed that virus‐related worries decreased over time, whereas economic worries remained largely constant. Moreover, the acceptance of NPIs considerably decreased over time. Virus‐related worries were positively associated with acceptance of NPIs, whereas this relationship was negative regarding economic worries (albeit smaller and less consistent). Unexpectedly, no interactions between virus‐related worries and economic worries were found. We conclude that individual differences in virus‐related and economic threat perceptions related to COVID‐19 play an important role in the acceptance of NPIs.